2021
DOI: 10.1186/s13023-021-01781-w
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea and blood transfusion therapy for Sickle cell disease in South Asia: inconsistent treatment of a neglected disease

Abstract: Background Hydroxyurea and blood transfusion therapies remain the main therapeutic strategies for Sickle cell disease. Preliminary data suggest substantial variation and inconsistencies in practice of these two therapeutic modalities in South Asia. In this systematic review we searched Medline, Cochrane library and Scopus for articles on usage of hydroxyurea and blood transfusion therapies for sickle cell disease in South Asia published in English between October 2005 and October 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Fixed-low dose hydroxyurea treatment (10 mg/kg/day) has shown encouraging outcomes in Indian SCD patients and may be appropriate for sickle patients from other South Asian nations who are of Indian descent. 9 Ataga et al conducted a randomized controlled trial of 198 sickle cell anemia patients and compared the efficacy of crizanlizumab with placebo and found that crizanlizumab therapy resulted in a significantly lower rate of sickle cell-related pain crises than placebo and was associated with a low incidence of adverse events. 10 It could be a potential treatment option for our patient for the prevention of further episodes of vaso-occlusive crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed-low dose hydroxyurea treatment (10 mg/kg/day) has shown encouraging outcomes in Indian SCD patients and may be appropriate for sickle patients from other South Asian nations who are of Indian descent. 9 Ataga et al conducted a randomized controlled trial of 198 sickle cell anemia patients and compared the efficacy of crizanlizumab with placebo and found that crizanlizumab therapy resulted in a significantly lower rate of sickle cell-related pain crises than placebo and was associated with a low incidence of adverse events. 10 It could be a potential treatment option for our patient for the prevention of further episodes of vaso-occlusive crisis.…”
Section: Discussionmentioning
confidence: 99%
“…This small-molecule drug is able to attach to and stabilize hemoglobin, preventing hemoglobin polymerization (i.e., formation of abnormal hemoglobin) that causes the formation of sickle shaped red blood cells [ 88 ]. In well-resourced countries, three potential treatments are available for preventing or reducing the morbidity and mortality associated with SCA: transfusions, hydroxyurea, and stem cell transplantation [ 89 ]. There is no evidence of any benefits of corticosteroid use in SCD acute events [ 90 ].…”
Section: Current Treatments Of Sickle Cell Diseasementioning
confidence: 99%
“…Malaria parasites, however, are now resistant to these drugs [ 9 ]. Hydroxyurea therapy for sickle cell disease has been utilized for many years and appears to be helpful for both the main and secondary prevention of stroke in sickle patients [ 12 ]. It does so by elevating the HbF levels that are present in the RBCs of patients.…”
Section: Reviewmentioning
confidence: 99%